Hubungan motivasi belajar dengan hasil belajar ips peserta didik kelas iv sekolah dasar - Aisyah Isnaini Wulandari; Retno Winarni; Supianto Supianto (Universitas Sebelas Maret, 2024)
This study aims to determine the correlation between learning motivation and learning outcomes in IPS among fourth-grade students at SDN Karangasem 1 and III Surakarta. It employs a quantitative research approach with a simple correlational method. The data sources include a learning motivation questionnaire and midterm exam results in the IPS subject. The sampling technique used is purposive sampling. Data collection involved distributing the learning motivation questionnaire and analyzing students' learning outcome documents. The validity was tested using the Gregory technique. Data analysis utilized tests for normality, linearity, simple correlation, and coefficient of determination. The results indicate a very strong correlation between learning motivation and IPS learning outcomes among fourth-grade students at SDN Karangasem 1 and III Surakarta.